Density and spatial distribution of different development stages of Sternechus subsignatus Boheman (Coleoptera: Curculionidae) in soybean crops - Socías, María Guillermina (2014)
The population recruitment and the spatial distribution of eggs, larvae, overwintering stages and adults of the soybean stalk weevil, Sternechus subsignatus Boheman, on soybean were estimated in two commercial farms of the Tucuman province, Argentina, during three consecutive productive cycles. At weekly intervals 30 sampling units were taken in a random distribution from each farm, and the number of adults as well as the number of ?rings? and gall-like structures around stems and/or branches recorded, from which the number of eggs and larvae, respectively, were inferred. At fortnightly intervals 20 sampling units of soil were taken at random and the number of overwintering stages recorded. The recruited number of the different developmental stages was analyzed by nested ANOVA, and the spatial distribution was estimated by the Taylor´s Power law and Iwao´s regression methods. Adults were recorded in all samples while eggs and larvae were found from mid-January to late April. The recruited number of the different stages was low and did not differ between stages or farms, and the spatial disposition of all developmental stages was at random. This study constitutes the first of its kind for this pest, and provides information that will be useful for the purposes of monitoring for biological studies and for insect pest control in the field.